Faith and Scientific Knowledge - Vladimir Vorobyev; Aleksandr Shchelkachev (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия I. Богословие, философия, 2012)
This article is devoted to the problem of the relationship between science and religion. The authors provide a comprehensive view of the way religious faith is rooted in the works of European science from its beginnings to our own days. Special attention is given to the atheistic attempts to discredit this notion, a position which once dominated the sciences in Russia, but which has today been shown to have outlived its relevance